Intervensi Kuasa Pengetahuan Terhadap Risiko Stunting Pada Masyarakat Pesisir : (Kasus Pada Kampung KB Pantai Kuranji) - Syuhada, Khalifatul; Fitriani, Ruslina; Septia, Firda R.; Novia, Intan; Karjono, M. (Prodi Sosiologi Universitas Mataram, 2024)
This research discusses about the power-knowledge mechanism in intervening in community behavior in order to reduce stunting rates in the coastal communities of Kuranji, West Lombok. The Kuranji coastal area of West Lombok has fish resources that can be accessed easily. However, there are still people who experience stunting. The purpose of this study is to analyze knowledge power intervention on the risk of stunting in the community of Kuranji community of West Lombok. The analysis uses the theoretical concepts put forward by Michel Foucault about the power of knowledge. This research uses qualitative research method, case study approach. While data collection data collection focuses on in-depth interviews, observation. The data obtained was analyzed through the stages of condensation, presentation, and conclusion. The results of this study indicate the existence of a knowledge power intervention knowledge power intervention on stunting cases in the community on the Kuranji coastline which is divided into into two, namely: sensitive interventions and specific interventions carried out from upstream to downstream from upstream to downstream. The form of the mechanism is implementation based on government regulations carried out starting from the grassroots, namely cadres cadres: i) conducting routine posyandu on pregnant women, infants, toddlers, postpartum mothers; ii) accompanying the postpartum mothers; ii) assisting adolescent and elderly posyandu, iii) providing voluntary counseling to adolescents, elderly counseling voluntarily to adolescents, the elderly, pregnant women, postpartum women; iv) providing supplementary food and modeling in providing.